Cyfres Pen Dafad - Llŷn, Anni (Y Lolfa, 2018)
A humorous adventure set in the world of spying and incredible gadgets. Special Agent Alys is the Welsh Alex Ryder! A first novel by television presenter Anni Llŷn. Intro – 1 - FEDRI DI GADW CYFRINACH? – 2 - MAE YSBÏWR DA YN ANWELEDIG – 3 - YSGOL BREIFAT 'HYNOD LEWYRCHUS' PEN Y RHYCH – 4 - CHWERTHIN PERYGLUS – 5 - AMSER CINIO, AMSER YSBÏO – 6 - DYSGU GWERS – 7 - NOS DA, NOS DRWG – 8 - YN Y BORE MAE 'I DAL HI! – 9 - MAE'N GAS GEN I GWSTARD! – 10 - HEDDIW.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books